Neurophysiological mechanisms involved in auditory perceptual organization - Bidet-Caulet, Aurélie; Bertrand, Olivier (Frontiers in Neuroscience, 2009)
In our complex acoustic environment, we are confronted with a mixture of sounds produced by several simultaneous sources. However, we rarely perceive these sounds as incomprehensible noise. Our brain uses perceptual organization processes to independently follow the emission of each sound source over time. If the acoustic properties exploited in these processes are well-established, the neurophysiological mechanisms involved in auditory scene analysis have raised interest only recently. Here, we review the studies investigating these mechanisms using electrophysiological recordings from the cochlear nucleus to the auditory cortex, in animals and humans. Their findings reveal that basic mechanisms such as frequency selectivity, forward suppression and multi-second habituation shape the automatic brain responses to sounds in a way that can account for several important characteristics of perceptual organization of both simultaneous and successive sounds. One challenging question remains unresolved: how are the resulting activity patterns integrated to yield the corresponding conscious perceptsµ